How cells wrap around coronavirus-like particles using extracellular filamentous protein structures - Sarthak Gupta; Christian D. Santangelo; Alison E. Patteson; J. M. Schwarz (Physical Review Research)
Nanoparticles, such as viruses, can enter cells via endocytosis, a process by which the cell membrane wraps around them. The role of nanoparticle size and shape on endocytosis has been well studied, but the biophysical details of how extracellular proteins on the cell membrane surface mediate uptake are less clear. Motivated by recent discoveries regarding extracellular vimentin in viral and bacterial uptake and the structure of coronaviruses, we construct a computational model with a cell-like and virus-like construct containing filamentous protein structures protruding from their surfaces. We study the impact of these additional degrees of freedom on viral wrapping. The cell surface is modeled as a deformable sheet with bending rigidity, and extracellular vimentin as semiflexible polymers, or extracellular components (ECC), placed randomly on the sheet. The virus is modeled as a deformable shell that also has explicit, freely rotating spike filaments on its surface. Our results indicate that cells with optimally populated filaments are more susceptible to infection as they take up the virus more quickly and utilize a relatively smaller area of the cell surface. At optimal ECC density, the cell surface forms a fold around the virus, which is faster and more efficient at wrapping than localized crumples. Additionally, cell surface bending rigidity aids in the generation of folds by increasing force transmission across the surface. Changing other mechanical parameters, such as the stretching stiffness of filamentous ECC or virus spikes, can result in localized crumple formation on the cell surface. We conclude with the implications of our study on the evolutionary pressures of virus-like particles, with a particular focus on the cellular microenvironment.